Is cortisol the key to the pathogenesis of delirium after coronary artery bypass graft surgery? - Kazmierski, Jakub (BioMed Central, 2011)
Postoperative delirium is a serious complication of cardiac surgery. However, the pathophysiology of this mental syndrome is largely unknown. Recent findings suggest an association between elevated level of cortisol and postoperative delirium. Further studies should investigate the mechanisms responsible for excessive perioperative cortisol secretion.